THE INFLUENCE OF WORLD WAR II ON ENGLISH LITERATURE: A CRITICAL ANALYSIS OF ELIE WIESEL’S NIGHT - Metin, Irmak (University of Kuningan, 2025)
World War II profoundly influenced English literature, particularly through the emergence of Holocaust narratives that document trauma, survival, and moral ambiguity. Elie Wiesel’s Night is one of the most significant literary testimonies of the Holocaust, offering a firsthand account of the atrocities experienced in Nazi concentration camps. This study critically examines Night in the broader context of postwar literature, exploring its contributions to trauma representation, memory transmission, and ethical dilemmas. Through a meta-synthetic analysis of scholarly works, this research addresses three key questions: (1) How does Night contribute to the understanding of trauma and memory in postwar literature? (2) What are the key literary and ethical elements in Night that differentiate it from other Holocaust narratives? and (3) How has the reception of Night evolved in educational and literary discourse over time? Findings reveal that Night employs fragmented narration, silence, and minimalist prose to convey the ineffability of trauma, reinforcing its literary and psychological impact. Additionally, the memoir’s rejection of sentimentalism and its portrayal of survival as morally ambiguous set it apart from other Holocaust accounts. Over time, Night has transitioned from relative obscurity to a foundational text in Holocaust education and global memory studies, shaping discussions on genocide prevention and ethical witnessing. This study underscores Night's enduring relevance in literature, history, and ethics, advocating for continued scholarly engagement with its themes in contemporary discourse on trauma and human rights.